2020
DOI: 10.1128/jvi.01677-19
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Newcastle Disease Virus as an Oncolytic Vector for Intratumoral Delivery of Immune Checkpoint Inhibitors and Immunocytokines

Abstract: Newcastle disease virus (NDV) is an attractive candidate for oncolytic immunotherapy due to its ability to replicate in tumor cells and potentially to overcome the inherently immunosuppressive nature of the tumor microenvironment. The advent of checkpoint blockade immunotherapy over the past few years represents a paradigm shift in cancer therapy. However, the prevalence of severe immune-related adverse events with CTLA4 and PD1 pathway blockade in clinical studies, especially in combination therapy groups, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 64 publications
2
48
0
Order By: Relevance
“…anti-CTLA-4 or NDV-antiPDL1-mIL-12 plus i.p. anti-CTLA-4 resulting in complete responses in 77 or 70%, respectively of mice bearing 9 day-old B16F10 flank tumors (277). The same treatments of one of two bilateral tumors resulted in 10 and 62% complete responses, respectively, of untreated tumors (277).…”
Section: Other Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-CTLA-4 or NDV-antiPDL1-mIL-12 plus i.p. anti-CTLA-4 resulting in complete responses in 77 or 70%, respectively of mice bearing 9 day-old B16F10 flank tumors (277). The same treatments of one of two bilateral tumors resulted in 10 and 62% complete responses, respectively, of untreated tumors (277).…”
Section: Other Virusesmentioning
confidence: 99%
“…Newcastle disease virus (NDV) is an oncolytic, enveloped, negative-sense, single-stranded RNA virus. NDVs have been engineered to express checkpoint inhibitor molecules and checkpoint inhibitor-cytokine conjugates (277). Although the antitumor activity of i.t.…”
Section: Other Virusesmentioning
confidence: 99%
“…Many studies have characterized immunological responses to oncolytic viruses and support immunotherapeutic value of tumor-specific viruses. To enhance the immunotherapeutic response, oncolytic viruses are being explored in combination with other immunomodulatory approaches such as cytokines and immune checkpoint inhibitors [ 13 , 14 ]. Given that oncolytic viruses were not adapted to trigger higher immune responses to begin with, is it surprising that their immune-activation activities are sub-par?…”
Section: Introductionmentioning
confidence: 99%
“…Vijayakumar and colleagues demonstrated that the recombinant NDV expressing the checkpoint inhibitor (anti-CTLA-4) worked together with radiotherapy to enhance tumor clearance of murine melanoma, indicating NDV is an effective immunotherapy agent capable of transgenic expression of single-chain variable fragment antibody in vivo to spare systematic exposure [ 96 ]. They also generated the recombinant NDVs expressing mAbs (PD1/PD-L1 antibody), superagonists (CD28) and immunocytokines (IL-12) and found that the viruses induced tumor control and survival benefits in a highly aggressive murine melanoma model [ 97 ]. These studies ingeniously combine two biological features of NDV, i.e., oncolytic activity and gene delivery capacity, together in immunotherapy for tumors, which further extends the range of clinical application of the NDV vector in human medicine.…”
Section: Recent Advances In the Development Of Ndv-vectored Vaccinmentioning
confidence: 99%